On the global impact of the Russian October Revolution of 1917 - Bebler, Anton (Prispevki za novejšo zgodovino, 2018)
The 1917 Russian October Revolution upset the political order in Europe, causing a significant geopolitical change on two continents and exerting various degrees of influence on the politics on six continents for several decades. However, the Revolution failed in its primary declared strategic objective - to destroy and abolish world capitalism. Moreover, it became discredited in its own country of origin and in most of Europe - much more than in many non-European countries, particularly Asia.
Keywords: Evropa; komunizem; mednarodni odnosi; oktobrska revolucija 1917; Rusija; zgodovina